Persistent pulmonary hypertension of the newborn. Issue 3 (9th February 2021) - Mandell, Erica; Kinsella, John P.; Abman, Steven H.
Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is a significant clinical problem characterized by refractory and severe hypoxemia secondary to elevated pulmonary vascular resistance resulting in right‐to‐left extrapulmonary shunting of deoxygenated blood. PPHN is associated with diverse cardiopulmonary disorders and a high early mortality rate for infants with severe PPHN. Surviving infants with PPHN have an increased risk of long‐term morbidities. PPHN physiology can be categorized by (1) maladaptation: pulmonary vessels have normal structure and number but have abnormal vasoreactivity; (2) excessive muscularization: increased smooth muscle cell thickness and increased distal extension of muscle to vessels that are usually not muscularized; and (3) underdevelopment: lung hypoplasia associated with decreased pulmonary artery number. Treatment involves adequate lung recruitment, optimization of cardiac output and left ventricular function, and pulmonary vasodilators such as inhaled nitric oxide. Infants who fail to respond to conventional therapy should be evaluated for lethal lung disorders including alveolar‐capillary dysplasia, T‐box transcription factor 4 gene, thyroid transcription factor‐1, ATP‐binding cassette A3 gene, and surfactant protein diseases.